Portuguese Experience With IFRS Adoption As Perceived By Auditors - Silva, Ana Paula (2022)
Purpose: Drawing on the experience of adoption of a model based on the International Financial Reporting Standards (IFRS) by Portuguese non-financial unlisted companies in 2010, called Sistema de Normalização Contabilística (SNC), this paper explores auditors’ perceptions regarding dimensions of relevance and suitability of the new accounting model to the Portuguese setting, major problems encountered, and the main engendered benefits. Methodology: An interpretative approach based on qualitative research methods was adopted, in which sixteen interviews with statutory auditors were conducted from a vantage point in 2017, seven years after the formal implementation of the IFRS-based model. Findings: Evidence suggests enduring problems but mostly a significant level of legitimation and institutionalization of the IFRS-based model: (i) the perceived motivations for SNC adoption are a good fit with the theoretically acknowledged motivations underlying accounting convergence; (ii) the principle-based standards and the fair value were largely perceived favorably; and (iii) the IFRS-based model brought about a number of benefits as expected ex ante. Implications: Findings shed light on the potential of the IFRS model to conform to countries whose accounting systems are remarkably disparate – as it was in Portugal – and offer an agenda for regulators and local and international policymakers. Originality and value: This study contributes to the accounting literature on IFRS adoption by providing empirical evidence from a European country that posited an a priori adverse context.